Inline spectroscopic measurements and LES of competitive consecutive reaction in a confined liquid jet in coflow. (15th March 2023) - Cameron Ahmad, M.R.; Usta, Mustafa; Pathikonda, Gokul; Khan, Irfan; Gillis, Paul; Dhodapkar, Shrikant; Jain, Pradeep; Ranjan, Devesh; Aidun, Cyrus K.
Highlights: Selectivity of competitive consecutive Bourne reaction in jet in coflow mixer. Non-intrusive experimental measurements of competitive consecutive Bourne Reaction. LES modeling of competitive consecutive Bourne Reaction. Abstract: Dynamic inline spectroscopic measurements and Large Eddy Simulation (LES) observe the products of a competitive-consecutive test reaction system within a well-characterized coaxial flow. The test reaction is a competitive consecutive chemistry which produces two spectrophotometrically measurable products. For the first time, these products are measured spatially throughout the reactor. Experimental and computational results map the reaction progress and product distribution. The evolution of this chemical process is explained in terms of the inlet, jet, and pipe flow regimes of the confined jet. The inlet and jet regimes were demonstrated to produce the majority of the desired product, whereas the undesired product is predominantly generated in the pipe regime.